Active subfractions of Abelmoschus esculentus substantially prevent free fatty acid-induced β cell apoptosis via inhibiting dipeptidyl peptidase-4 - Huang, Chien-Ning (PLoS One, 2017)
Lipotoxicity plays an important role in exacerbating type 2 diabetes mellitus (T2DM) and leads to apoptosis of β cells. Recently dipeptidyl peptidase-4 (DPP-4) inhibitors have emerged as a useful tool in the treatment of T2DM. DPP-4 degrades type 1 glucagon-like peptide (GLP-1), and GLP-1 receptor (GLP-1R) signaling has been shown to protect β cells by modulating AMPK/mTOR, PI3K, and Bax. The anti-hyperglycemic effect of Abelmoschus esculentus (AE) is well known, however its mucilage makes it difficult to further examine this effect. In our recent report, a sequence of extraction steps was used to obtain a series of subfractions from AE, each with its own composition and property. Among them F1 (rich in quercetin glucosides and pentacyclic triterpene ester) and F2 (containing large amounts of carbohydrates and polysaccharides) were found to be especially effective in attenuating DPP-4 signaling, and to have the potential to counter diabetic nephropathy. Hence, the aim of the present study was to investigate whether AE subfractions can prevent the palmitate-induced apoptosis of β cells, and the putative signals involved. We demonstrated that AE, and especially 1 μg/mL of F2, decreased palmitate-induced apoptosis analyzed by flow cytometry. The result of western blot revealed that palmitate-induced decrease in GLP-1R and increase in DPP-4 were restored by F1 and F2. The DPP-4 inhibitor linagliptin decreased the expression of caspase 3, suggesting that DPP-4 is critically involved in apoptotic signaling. Analysis of enzyme activity revealed that palmitate increased the activity of DPP4 nearly 2 folds, while F2 especially inhibited the activation. In addition, AMPK/mTOR, PI3K and mitochondrial pathways were regulated by AE, and this attenuated the palmitate-induced signaling cascades. In conclusion, AE is useful to prevent the exacerbation of β cell apoptosis, and it could potentially be used as adjuvant or nutraceutical therapy for diabetes.